(untitled) (CIPEEX, 2024)
Studying workers’ health is essential to prevent diseases and accidents, understand the relationship between quality of life and productivity and satisfaction, and protect workers’ rights. Currently, concern for workers’ quality of life is directly related to their physical, mental, and psychological well-being. The objective of the study was to evaluate the quality of life of workers in the Vale do São Patrício-Goiás. This is a cross-sectional study approved by the CEP, under number 6.436.246. The evaluation was carried out using the question “How do you evaluate your quality of life?” from the WHOQOL-bref questionnaire, and the data were analyzed using the Chi-square test. The study included 704 workers, 62.2% of whom were women, with an average age of 39.01 years (±12.28). A good perception of quality of life was evidenced in 78.9% of men and 69.6% of women (P=0.026); educational level with doctorate/post-doctorate (P=0.061); and with a workload of up to 40 hours per week (P=0.098). These findings highlight the importance of interventions aimed at improving workers’ quality of life.